Key Amino Acid Residues of the Agt1 Transporter for Trehalose Transport by Saccharomyces cerevisiae - Anqi Chen; Yuhan Cheng; Liushi Meng; Jian Chen (Journal of Fungi)
Trehalose is crucial for the stress resistance of Saccharomyces cerevisiae, primarily through its stabilization of proteins and membranes. The Agt1 transporter, a member of the Major Facilitator Superfamily, mediates trehalose uptake, a key process for maintaining cellular integrity under stress. Despite its importance, the molecular mechanisms of Agt1-mediated trehalose transport remain underexplored. In this study, we expressed and purified the trehalase enzyme TreA from E. coli to develop reliable trehalose assays. We screened 257 wild S. cerevisiae isolates, identifying strains with enhanced trehalose transport capacities. Comparative analyses, including structural modeling and molecular docking, revealed that specific Agt1 variants exhibited significantly higher transport efficiency, influenced by key residues in the transporter. Molecular dynamics simulations and steered molecular dynamics provided further insights, particularly into the role of the Agt1 channel head region in substrate recognition and binding. Site-directed mutagenesis validated these findings, showing that mutations at critical residues, such as 156Q, 164L, 256Q, 395E, 396R, and 507Y significantly reduced transport activity, while 137Q, 230T, and 514 N increased efficiency under certain conditions.